2021
DOI: 10.3389/fnagi.2021.684743
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Engagement Metrics During Reactive Balance Are Associated With Distinct Aspects of Balance Behavior in Older Adults

Abstract: Heightened reliance on the cerebral cortex for postural stability with aging is well-known, yet the cortical mechanisms for balance control, particularly in relation to balance function, remain unclear. Here we aimed to investigate motor cortical activity in relation to the level of balance challenge presented during reactive balance recovery and identify circuit-specific interactions between motor cortex and prefrontal or somatosensory regions in relation to metrics of balance function that predict fall risk.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 98 publications
4
42
0
2
Order By: Relevance
“…We speculate that increased synchronization between prefrontal and motor cortical areas during balance recovery with aging may explain associations between cognitive function and balance control in older adults. For example, we recently showed that functional connectivity in the beta frequency band between motor and prefrontal cortical areas during balance recovery in older adults is associated with cognitive dual task interference in walking ( Palmer et al, 2021 ). A better understanding of the mechanisms linking balance and cognitive function in aging could reveal new therapeutic targets for rehabilitation and enable a more targeted exploration of the effects of cognitive training on balance rehabilitation ( Smith-Ray et al, 2015 ; Hagovska and Olekszyova, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that increased synchronization between prefrontal and motor cortical areas during balance recovery with aging may explain associations between cognitive function and balance control in older adults. For example, we recently showed that functional connectivity in the beta frequency band between motor and prefrontal cortical areas during balance recovery in older adults is associated with cognitive dual task interference in walking ( Palmer et al, 2021 ). A better understanding of the mechanisms linking balance and cognitive function in aging could reveal new therapeutic targets for rehabilitation and enable a more targeted exploration of the effects of cognitive training on balance rehabilitation ( Smith-Ray et al, 2015 ; Hagovska and Olekszyova, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased synchronization between prefrontal and motor cortical areas during balance recovery with aging may explain associations between cognitive function and balance control in older adults. For example, we recently showed that beta coherence between motor and prefrontal cortical areas during balance recovery in older adults is associated with cognitive dual task interference in walking (Palmer et al, 2021). A better understanding of the mechanisms linking balance and cognitive function in aging could reveal new therapeutic targets for rehabilitation and enable a more targeted exploration of the effects of cognitive training on balance rehabilitation (Smith-Ray et al, 2015;Hagovska and Olekszyova, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While studies in older populations have been limited, older adults generally have smaller and later cortical N1s (Duckrow et al 1999;Ozdemir et al 2018), with changes in temporal characteristics including the appearance of multiple component peaks in some individuals with reduced mobility (Duckrow et al 1999). We recently reported associations between larger N1 amplitudes, lower cognitive set shifting ability, stiffer balance recovery behavior, and increased antagonist muscle activity in older adults (Payne et al 2021), further implicating the cortical N1 in the relationship between balance and cognitive problems with aging. We now investigate the cortical N1 responses in a population of older adults with Parkinson's disease, who have both balance and cognitive impairments.…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, N1 amplitude in younger adults is associated with lower balance ability (Payne and Ting 2020a), a hallmark of Parkinson's disease (Bloem 1992;Grimbergen et al 2004;Koller et al 1989). Further, in older adults N1 amplitude is associated with lower cognitive set shifting ability and greater antagonist muscle activity (Payne et al 2021), both of which are associated with balance impairment in Parkinson's disease (Lang et al 2019;McKay et al 2018). All of these associations in unimpaired populations suggest the N1 would be larger in Parkinson's disease, related to greater cortical engagement to compensate for balance impairments, but there are also reasons to suspect the N1 might be reduced in Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%